Association between albumin changes and prognosis in older patients with acute myocardial infarction - Yang, Zhi-cheng; Zhang, Lei; Xi, Ying-bin; Jiang, Gui-hua; Lin, He; Pan, Hui; Wang, Zhi-hao (Frontiers in Medicine, 2025)
Background and aimsAcute myocardial infarction (AMI) is the leading cause of death in the world. Therefore, early identification of the prognosis of older patients with AMI are particularly urgent, and better to improve treatment. This study aimed to explore the association between albumin changes and prognosis in older patients with AMI.MethodsOutcomes included all-cause death during hospitalization, cardiac death, gastrointestinal hemorrhage, nonfatal myocardial infarction, acute heart failure, and severe arrhythmia. Multivariable-adjusted Cox regression analysis and curve fitting were used to assess the relationship between albumin changes and prognosis in patients with AMI.ResultsOur study included 288 older patients with AMI. A S-shaped association between the albumin changes and mortality of patients with AMI was found. For all-cause death, we found two inflection points were − 3.27 and 0.92 g/L. On the left side of −3.27 g/L, the OR was 0.41 (OR: 0.41, 95%CI: 0.32–0.64, p < 0.05). On the right side of 0.92 g/L, the OR was 0.58 (OR: 0.58, 95%CI: 0.34–0.86, p < 0.05). The OR was 2.12 between −3.27 and 0.92 g/L (OR: 2.12, 95%CI: 1.16–6.24, p < 0.05). For cardiac death, two inflection points were − 3.19 and 1.17 g/L. On the left side of −3.19 g/L, the OR was 0.45 (OR: 0.45, 95%CI: 0.28–0.79, p < 0.05). On the right side of 1.17 g/L, the OR was 0.63 (OR: 0.63, 95%CI: 0.38–0.86, p < 0.05). The OR was 4.53 between −3.19 and 1.17 g/L (OR: 4.53, 95%CI: 0.90–12.52, p > 0.05). After adjusting for all potential covariates, albumin changes were negatively associated with gastrointestinal hemorrhage (OR: 0.87; 95%CI: 0.81–0.94, p < 0.001). After adjusting for all potential covariates, albumin changes were negatively associated with acute heart failure (OR: 0.86; 95%CI: 0.75–0.99, p = 0.046).ConclusionOut findings showed that a S-shaped association between the albumin changes and mortality of older AMI patients, with the inflection of roughly −3.27 g/L and 0.92/L. And changes in albumin levels are negatively correlated with gastrointestinal bleeding and acute heart failure. These findings were helpful for the clinical treatment.